The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2277978717695154
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Inflation Crisis and Long-run Economic Growth in India: An Empirical Survey of Threshold Level of Inflation

Abstract: This article investigates the existence of a threshold level of inflation and how any such level affects the growth of Indian economy. The article also seeks to examine the dynamic short-run and long-run relationship between inflation and economic growth in India. By employing spline regression method to estimate the threshold level of inflation and the long-run and short-run relationships, the results show a statistically significant structural break in the relationship between inflation and economic growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
(39 reference statements)
2
12
0
1
Order By: Relevance
“…Conditional least squares econometric results show that low inflation has a positive impact on economic growth and the threshold level of inflation for GDP growth in Zimbabwe is 4 percent. The results of the study are consistent with the findings of Sattarov (2011) who found an optimal inflation rate of 4 per cent for the Finnish economy, Behera and Mishra (2017) who found a threshold level of inflation of 4 per cent in India, Masiyandima et al (2018) who found an optimal level of inflation of 4.6 per cent for the multicurrency regime (2009-2017) and 8.7 per cent for the period 1980 to 1997 in Zimbabwe, Singh (2010) who found a threshold level of inflation for India at 6 per cent, Iqbal and Nawaz (2009) who obtained 6 per cent inflation rate to be growth maximising in Pakistan, Sarel (1996) who found a threshold level of inflation of 8 per cent, Khan and Senhadji (2001) who found a threshold level of inflation for developing countries to be 11 per cent to 12 per cent, Hasanov (2011) who found an optimal inflation rate of 13 per cent for Azerbaijani economy and Ndoricimpa (2017) who found inflation threshold of 6.7 per cent for African countries and 9 per cent for lowincome countries. The study findings also show that lending rate has a negative impact on economic growth, where a 1 per cent increase in lending rate decreases economic growth by 0.0008881 per cent.…”
Section: Interpretation Of Econometric Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Conditional least squares econometric results show that low inflation has a positive impact on economic growth and the threshold level of inflation for GDP growth in Zimbabwe is 4 percent. The results of the study are consistent with the findings of Sattarov (2011) who found an optimal inflation rate of 4 per cent for the Finnish economy, Behera and Mishra (2017) who found a threshold level of inflation of 4 per cent in India, Masiyandima et al (2018) who found an optimal level of inflation of 4.6 per cent for the multicurrency regime (2009-2017) and 8.7 per cent for the period 1980 to 1997 in Zimbabwe, Singh (2010) who found a threshold level of inflation for India at 6 per cent, Iqbal and Nawaz (2009) who obtained 6 per cent inflation rate to be growth maximising in Pakistan, Sarel (1996) who found a threshold level of inflation of 8 per cent, Khan and Senhadji (2001) who found a threshold level of inflation for developing countries to be 11 per cent to 12 per cent, Hasanov (2011) who found an optimal inflation rate of 13 per cent for Azerbaijani economy and Ndoricimpa (2017) who found inflation threshold of 6.7 per cent for African countries and 9 per cent for lowincome countries. The study findings also show that lending rate has a negative impact on economic growth, where a 1 per cent increase in lending rate decreases economic growth by 0.0008881 per cent.…”
Section: Interpretation Of Econometric Resultssupporting
confidence: 92%
“…In order to detect the potential non-linear relationship between inflation and economic growth and estimate the threshold level of inflation, the study used the methodology proposed by Khan and Senhadji (2001) and used by Doguwa (2012) in Nigeria, Iqbal and Nawaz (2009) in Pakistan, Hasanov (2011) in Azerbaijani, Makuria (2013) in Ethiopia and Behera and Mishra (2017) in India. In order to determine the threshold level of inflation, the following econometric model was estimated.…”
Section: Threshold Model and The Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we control for inflation rate (LINF i,t ), which is measured by consumer price index (CPI), because many studies found that inflation has influences on countries' economic growth (Adebola & Dahalan, 2011;Behera & Mishra, 2017;Divya & Devi, 2014;Mallik & Chowdhury, 2001). Another control variable we added is the ratio of domestic credit delivered by the financial sector to GDP.…”
Section: Variablesmentioning
confidence: 99%